2002
DOI: 10.1021/ic0113146
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Purification, and Structural Characterization of the Dimethyldiselenoarsinate Anion

Abstract: A novel arsenic-selenium solution species was synthesized by reacting equimolar sodium selenite and sodium dimethylarsinate with 10 mol equiv of glutathione (pH 7.5) in aqueous solution. The solution species showed a single (77)Se NMR resonance at 112.8 ppm. Size-exclusion chromatography (SEC) using an inductively coupled plasma atomic emission spectrometer (ICP-AES) as the simultaneous arsenic-, selenium-, sulfur-, and carbon-specific detector revealed an arsenic-selenium moiety with an As:Se molar ratio of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…DMA III is also less toxic to cells in culture, likely because of the inability to target the vicinal dithiol of lipoic acid–containing enzymes of the Krebs cycle. It should be noted that a dimethyldiselenoarsinate anion (Gailer et al 2002a) has been synthesized in vitro , but has yet to be identified in either animal or cell culture studies. Formation of this compound could possibly facilitate uptake of selenium, although this has yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…DMA III is also less toxic to cells in culture, likely because of the inability to target the vicinal dithiol of lipoic acid–containing enzymes of the Krebs cycle. It should be noted that a dimethyldiselenoarsinate anion (Gailer et al 2002a) has been synthesized in vitro , but has yet to be identified in either animal or cell culture studies. Formation of this compound could possibly facilitate uptake of selenium, although this has yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…76,81 The rapid formation of [(GS) 2 AsSe] À in blood, 73 and its equally rapid biliary excretion (and thus the removal of highly toxic trivalent arsenic from the organism itself), suggests that the formation and excretion of [(GS) 2 AsSe] À represents an important mammalian detoxification mechanism. Any excess arsenite that is left over after this step in blood will be shuttled to the liver to undergo biomethylation (Scheme 1).…”
Section: Discussionmentioning
confidence: 99%
“…A metabolite containing glutathione (GSH) and equimolar amounts of As and Se, [(GS) 2 AsSe] − , was identified in bile from rabbits injected with selenite [Se(IV)] and As(III) (Gailer et al 2000). This metabolite is thought to be synthesized in hepatocytes (Gailer et al 2002a) and erythrocytes (Manley et al 2006) − can be synthesized chemically by reacting DMA(V) with GSH and Se(IV) (Gailer et al 2002b). Even though these metabolites are present in marine mammals, seabirds, and sea turtles, the levels may be low.…”
Section: Future Areas Of Studymentioning
confidence: 99%